From the "temple of God" to God as the temple a Biblical theological study of the temple in the Book of Revelation - Spatafora, Andrea 1958- (Roma Pontificia Università Gregoriana, 1997)
The term naos is found thirteen times in the Apocalypse, indicating the significant place it occupies within the book. To date, no complete study of the theme of the temple in this Book exists. Taking into consideration the scholarly contributions that have been made by those studying the book or the theme of the temple in the New Testament, the present work proposes an analysis of the verses containing the term naos in view of establishing John the Seer's use of temple imagery to speak of the Church. The study concludes by presenting the temple theology of the Book of Revelation including a comparison with the texts of the Old Testament, Jewish intertestamental literature and the New Testament with particular regard to the Fourth Gospel. Andrea Spatafora, 1958 , made profession in the Congregation of the Missionaries of the Holy Family and was ordained a priest in 1983. Completing a licentiate in Sacred Scripture at the Pontifical Biblical Institute in 1992, he obtained a doctorate in Biblical Theology at the Pontifical Gregorian University in 1997.
Zugl.: Rom, Pontificia Univ. Gregoriana, Diss., 1997
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Bibel; Tempel; Hochschulschrift